The Unspoken Morality of Childhood : Family, Friendship and the Wisdom of the Everyday. - Monroe, Kristen Renwick (Anthem Press, 2022)
The Unspoken Morality of Childhood: Parenting, Self-Esteem and the Significance of Character reflects the thoughts of a senior ethicist and discusses complex ethical concepts such as identity, agency, self-esteem, forgiveness, relations with our parents, dealing with loss, the moral imagination, and a wide range of other issues that people confront every day.